How divergent are children's divergent movements? The role of cognition and expertise in a class-randomized cross-over trial. (March 2023) - De Fano, Antonio; Benzing, Valentin; Condello, Giancarlo; Ballester, Rafael; Tocci, Nicoletta; Marchetti, Rosalba; Pesce, Caterina; Schmidt, Mirko
Abstract: This study aimed at investigating (1) the cognitive and motor predictors of divergent movement ability (DMA) in childhood and (2) the role of sport and enriched physical education (PE) experience. Participants were 165 fifth graders, aged 10–11 years, with different histories (onset and duration) of participation in enriched PE. They were assessed in cognitive/attentional and motor/sport skills and active play/sport habits at baseline, and six months later in DMA. Results of regression analyses showed an overall prediction of DMA by sport practice and a nuanced prediction of individual DMA indices (fluency, flexibility, originality) by decision making and spatial attention ability. Linear mixed models revealed better DMA in children exposed to enriched PE, with differential effects on DMA indices depending on its duration and earlier/later onset. The results identify novel cognitive determinants of children's DMA and suggest that sport practice and experience of designed enrichment in PE may benefit DMA. Highlights: Divergent movement ability (DMA) in children is predicted by cognitive functions. Sport practice, spatial attention and hot but not cool executive function predict DMA. Exposure to enriched physical education (PE) is associated with a higher DMA. Earlier/later onset and longer/shorter duration of the enriched PE experience matter.